Electric Pumps, Groundwater, Agriculture and Water Buyers: Evidence from West Bengal. Issue 11 (2nd November 2021) - Buisson, Marie-Charlotte; Balasubramanya, Soumya; Stifel, David
Abstract: Irrigation with electric pumps is cheaper than with diesel pumps in West Bengal where electricity and diesel are unsubsidised, and where pump owners typically irrigate their winter rice crop and often sell water to farmers who do not own pumps. Using purposefully selected primary data, we examine whether electric-pump owners have greater water access and rice production during the monsoon and winter seasons compared to diesel-pump owners and water buyers. We also examine whether electric pump-owners provide greater access to irrigation services through water sales. We find that electric-pump ownership increased agricultural outputs both at the extensive and intensive margins in both seasons. The number of clients served by electric-pump owners was greater than those served by diesel-pump owners, but there was only a small difference in total irrigated areas, suggesting that electric-pump owners sell water to farmers with smaller land holdings. The evidence indicates that in an environment where inadequate irrigation has been one of the factors constraining agriculture, electric pumps have the potential to support agricultural growth and generate pro-poor side effects.